Effect of Firing Temperature and Holding Time on Characterization of Al/SiC Metal Matrix Composites Produced by Pressureless Infiltration. - Zulfia, Anne; Ariati, Myrna (UI Scholars Hub, 2006)
Effect of Firing Temperature and Holding Time on Characterization of Al/SiC Metal Matrix Composites Produced by Pressureless Infiltration. The production of Al-SiC metal matrix composite can be carried out by pressureless metal infiltration processs (PRIMEX). The experiment was conducted using aluminium AC2B ingot as a matrix and 50%Vf SiC powder as a reinforcement which is mixed with 10% Mg powder for wetting agent. The variables of this experiment are holding time and firing temperature to investigate the effect of these conditions on mechanical properties of Al-SiC metal matrix composites. Holding time was conducted for 2,5,8,10,12 hours and firing temperatures was 750, 800, 900, 1000, 1100°C respectively.. The composites produced are analysed both mechanical properties and metalography such as densities, porosities, hardness, as well as wear rate. The results showed that the longer holding time and increasing firing temperature will increase mechanical properties of Al-SiC metal matrix composites, and it is found that the optimum mechanical properties at 1000°C for 10 hour.